Aristolochia phoenixa, a new species of Aristolochiaceae from Hainan Island, China - Xue, Miao-Ya; Huang, Rui-Zhou; Yang, Hai-Jun; Lu, Chun-Yang; Xu, Han (Phytotaxa, 2025)
Aristolochia phoenixa is described and illustrated as a new species of Aristolochiaceae from Hainan Island, China. This species is morphologically similar to A. ledongensis and Isotrema sanyaense in the shape of leaf blade and calyx. However, A. phoenixa can be easily distinguished from these two species by its pedicel (1.8–2.2 cm vs. 0.7–1.0 cm, 1.1–2.6 cm), size of basal tube (ca. 20.0–26.0 × 5.0–6.0 mm vs. ca. 15.0–16.0 × 4.5–5.0 mm, ca. 22 × 5 mm) and throat (without spots vs. with dark red–brown spots, without spots), and the flowering time (November–December vs. August, October).